Communication skills: a mandatory competence for ground and airplane crew to reduce tension in extreme situations - Vieira, Ana Maria (2019)
Made available in DSpace on 2019-09-12T16:32:36Z (GMT). No. of bitstreams: 0 Previous issue date: 2010